Presentations of rings with a chain of semidualizing modules - Amanzadeh, Ensiyeh; Dibaei, Mohammad T. (MATHEMATICA SCANDINAVICA, 2017)
Inspired by Jorgensen et al., it is proved that if a Cohen-Macaulay local ring R with dualizing module admits a suitable chain of semidualizing R-modules of length n, then RQ/(I_1+… +I_n) for some Gorenstein ring Q and ideals I_1,… , I_n of Q; and, for each Λ [n], the ring Q/(_Λ I_) has some interesting cohomological properties. This extends the result of Jorgensen et al., and also of Foxby and Reiten.